The effect of diabetes on the risk and mortality of acute lung injury/acute respiratory distress syndrome: A meta-analysis - Ji, Mingxia (Medicine (Baltimore), 2019)
BACKGROUND: The role of pre-existing diabetes in acute lung injury/acute respiratory distress syndrome (ALI/ARDS) is still controversial. This systematic review and meta-analysis of observational studies aimed to evaluate the effect of diabetes on the risk and mortality of ALI/ARDS. METHODS: A comprehensive literature search was performed in PubMed, Scopus, Cochrane Central Register of Controlled Trails and Web of Science for their inception to September 2018. Summary risk estimates were calculated with a DerSimonian and Laird random-effects model. Heterogeneity was evaluated using Cochran chi-square test and the I(2) statistic. RESULTS: Ultimately, 14 studies with a total of 6613 ALI/ARDS cases were included. The risk of ALI/ARDS was not significantly reduced in diabetes patients (OR 0.82, 95% CI 0.57–1.18, P = .283), with obvious heterogeneity across studies (I(2) = 72.5%, P < .001). Further analyses in the meta-analysis also showed no statistically significant associations between pre-existing diabetes and in-hospital mortality (OR 0.79, 95% CI 0.51–1.21, P = .282) or 60-day mortality of ALI/ARDS (OR 0.91, 95% CI 0.75–1.11, P = .352). CONCLUSION: This systematic review and meta-analysis of observational studies indicates that pre-existing diabetes have no effect on the risk and mortality of ALI/ARDS.